2017
DOI: 10.1101/176545
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Requirements for coregistration accuracy in on-scalp MEG

Abstract: Optically-pumped magnetometers (OPMs) have recently reached sensitivity levels that enable their use in magnetoencephalography (MEG). In contrast to the SQUID sensors used in current MEG systems, OPMs do not require cryogenic cooling and can thus be placed within millimetres from the head, enabling the construction of on-scalp sensor arrays that conform to the shape of the head. To properly estimate the location of neural sources within the brain, one must accurately know the position and orientation of sensor… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…We have previously shown that the optical coregistration method we applied in the OPM measurement is sufficiently accurate for on‐scalp MEG (Zetter et al, , ). Thus, coregistration error should not be the limiting factor when improving OPM source estimates beyond those obtained from SQUID data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously shown that the optical coregistration method we applied in the OPM measurement is sufficiently accurate for on‐scalp MEG (Zetter et al, , ). Thus, coregistration error should not be the limiting factor when improving OPM source estimates beyond those obtained from SQUID data.…”
Section: Discussionmentioning
confidence: 99%
“…With open‐loop OPMs—such as the ones used here—crosstalk mainly changes the gain of the sensor and the orientation of its sensitive axis (Tierney et al, ). If crosstalk is not taken into account, it will cause source‐estimation errors (Zetter et al, ). We do not believe that crosstalk will be a severe issue in dense open‐loop OPM arrays.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Optically pumped magnetometers (OPMs) have attracted increasing attention in neuroscientific research over the last few years (e.g., Alem et al, 2014;Boto et al, 2017Boto et al, , 2018Hill et al, 2019;Iivanainen et al, 2020;Roberts et al, 2019;Zetter et al, 2018). Without the need to be cooled to cryogenic temperatures like superconducting quantum interference device (SQUID) magnetometers, OPMs require relatively minimal insulation and do not need to be mounted at fixed locations within a dewar like traditional MEG.…”
Section: Introductionmentioning
confidence: 99%